Working from home during the COVID-19 outbreak in Sweden: effects on 24-h time-use in office workers - David M. Hallman; Leticia Bergamin Januario; Svend Erik Mathiassen; Marina Heiden; Sven Svensson; Gunnar Bergström (BMC, 2021)
Abstract Background The COVID-19 pandemic has triggered national recommendations encouraging people to work from home (WFH), but the possible impact of WFH on physical behaviors is unknown. This study aimed to determine the extent to which the 24-h allocation of time to different physical behaviors changes between days working at the office (WAO) and days WFH in office workers during the pandemic. Methods Data were collected on 27 office workers with full-time employment at a Swedish municipal division during the COVID-19 outbreak in May-July 2020. A thigh-worn accelerometer (Axivity) was used to assess physical behavior (sedentary, stand, move) during seven consecutive days. A diary was used to identify periods of work, leisure and sleep. 24-h compositions of sedentary, standing and moving behaviors during work and non-work time were examined using Compositional data analysis (CoDA), and differences between days WAO and days WFH were determined using repeated measures ANOVA. Results Days WFH were associated with more time spent sleeping relative to awake, and the effect size was large (F = 7.4; p = 0.01; ηp 2 = 0.22). The increase (34 min) in sleep time during WFH occurred at the expense of a reduction in work and leisure time by 26 min and 7 min, respectively. Sedentary, standing and moving behaviors did not change markedly during days WFH compared to days WAO. Conclusion Days working from home during the COVID-19 pandemic in Sweden were associated with longer duration of sleep than days working at the office. This behavioral change may be beneficial to health.